Review of the genus Afronaso Jacobi, 1910 (Hemiptera: Fulgoroidea, Caliscelidae), with the description of two new genera and a new species from tropical Africa and Madagascar - Gnezdilov, Vladimir M.; Neimorovets, Vladimir V. (Zootaxa, 2025)
The caliscelid genus Afronaso Jacobi, 1910 is reviewed, with a male of Afronaso cuneiceps (Fennah, 1957) described and illustrated for the first time. Savanopulex Dlabola, 1987 is placed in synonymy under Afronaso Jacobi, 1910 and Savanopulex endroedyi Dlabola, 1987 is placed in synonymy under Afronaso cuneiceps (Fennah, 1957). A new species, Afronaso pumilio Gnezdilov, sp. nov., is described from Uganda. A new genus, Rhinomada Gnezdilov, gen. nov., is erected to accommodate two Madagascan species, Afronaso gryphus Gnezdilov et Bourgoin, 2009 (type species) and A. malagasicus Gnezdilov et Bourgoin, 2009, with new combinations proposed—Rhinomada gryphus (Gnezdilov et Bourgoin, 2009), comb. nov. and Rh. malagasica (Gnezdilov et Bourgoin, 2009), comb. nov. A new genus, Albrehmus Gnezdilov, gen. nov., is erected to accommodate Issopulex chloe Linnavuori, 1973, recorded for the first time from Egypt and Erithrea, with a new combination proposed—Albrehmus chloe (Linnavuori, 1973), comb. nov. The relationships of the genera Afronaso Jacobi, 1910, Albrehmus Gnezdilov, gen. nov., Calampocus Gnezdilov et Bourgoin, 2009, Issopulex China et Fennah, 1960, and Rhinomada Gnezdilov, gen. nov. within the tribe Caliscelini are discussed. Key to species of the genera Afronaso Jacobi and Rhinomada Gnezdilov, gen. nov. are given.